The Influence of PHBS and CTPS Education on Increasing Student Knowledge at SD Negeri 04 Air Hitam Village, Datuk Lima Puluh District - Hasibuan, Rapotan; Annisa, Rifa; Handoko, Fauziah; Andwina; Paramitha, Lydia; Witriani, Eca; Qur-ani, Oktafera Halmi; Refiana, Revail (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This study aims to increase knowledge and awareness of clean and healthy living behavior (PHBS) and handwashing with soap (CTPS) in fourth grade students at SD Negeri 04 Air Hitam Village, Batubara Regency through interactive and participatory educational activities. Method: The method used was a quantitative pre-experimental study with a one-group pre-test and post-test design involving 49 fourth-grade students. Educational activities included interactive lectures, discussions, CTPS practice simulations using songs, illustrative images, and educational games tailored to the children's characteristics. Practical Applications: The results showed a significant increase in the average knowledge score from 6.35 to 8.12, as well as an increase in the proportion of students with good knowledge from 61.2% to 91.8%. Furthermore, students demonstrated high enthusiasm and a temporary change in attitudes toward handwashing practices. Teachers responded positively and stated the need for similar, ongoing activities to support the formation of healthy habits. Challenges to implementation included limited handwashing facilities, crowded classrooms, and limited time. Conclusion: This study emphasizes the importance of a holistic approach involving teachers, parents, and facility management so that the implementation of PHBS and CTPS can be sustainable and have a real impact on behavioral changes in the school environment.